Afucosylated IgG in idiopathic nephrotic syndrome patients with anti-nephrin autoantibodies correlate with disease activity - Sonia Spinelli; Andrea Garbarino; Francesca Lugani; Edoardo La Porta; Noemi Rumeo; Giorgio Piaggio; Alberto Magnasco; Antonella Trivelli; Maria Ludovica Degl’Innocenti; Gino Tripodi; Simona Granata; Francesca Leone; et al. (Journal of Translational Autoimmunity)
Background: Idiopathic nephrotic syndrome (INS) is a glomerular disorder characterized by podocyte injury and proteinuria. Emerging evidence suggests that anti-nephrin autoantibodies (Abs) may contribute to disease pathogenesis in a subset of INS patients. Variation in techniques for detecting anti-nephrin Abs and lack of urinary data contribute to uncertainties of results.While reduced IgG fucosylation is known to enhance antibody-dependent cellular cytotoxicity in non-INS autoimmune diseases, its role in modulating anti-nephrin autoantibody function and disease severity in INS remains unexplored. Methods: We studied serum and urine of pediatric and young adult patients with biopsy-proven focal segmental glomerulosclerosis (FSGS) or minimal change disease (MCD) with different disease activity (proteinuria + vs proteinuria-). Anti-nephrin autoantibodies were evaluated with either conventional ELISA and immunoprecipitation using recombinant full-length extracellular domain of FLAG tagged human nephrin. Aleuria Aurantia Lectin (AAL) and Ulex Europaeus Agglutinin I (UEA-I) Lectins assessed IgG autoantibody fucosylation. Results: Anti-nephrin autoantibodies were detected in serum of 11 % of FSGS and 15 % of MCD patients, with a higher prevalence among those with nephrotic-range proteinuria. These autoantibodies were absent in healthy controls as well as in patients with primary membranous nephropathy and class V lupus nephritis. Autoantibody titers correlated with disease activity, decreasing during remission. Immunoprecipitation confirmed results obtained with ELISA. In a subset of anti-nephrin positive patients, the autoantibodies were also detected in urine. Circulating anti-nephrin autoantibodies showed significantly reduced antennary and core fucosylation of IgG. Conclusions: Our findings confirmed the significance of anti-nephrin autoantibodies as markers of active disease in a small subset of INS patients and showed their presence in urine. ELISA and Immunoprecipitation results correlated. Molecular studies showed that altered IgG fucosylation may contribute to immune-mediated podocyte injury. These insights provide potential biomarkers for disease monitoring and therapeutic targets in INS.